2011
DOI: 10.1039/c1cc10563a
|View full text |Cite
|
Sign up to set email alerts
|

A simple and label-free sensor for mercury(ii) detection in aqueous solution by malachite green based on a resonance scattering spectral assay

Abstract: Mercury ions (Hg(2+)) can specifically interact with the thymine-rich Hg(2+) aptamer and malachite green (MG) to form the Hg(2+) aptamer-MG-Hg(2+) complex, inducing the increase of resonance scattering (RS) intensity at 611 nm, which enables the label-free detection of Hg(2+) in aqueous solution with high selectivity and a detection limit of 1.7 nM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…The environmental pollution caused by mercury ion has become a global problem; therefore, developing a sensitive and selective method for the detection of Hg 2+ ions is very necessary. Until now, numerous detection methods based on fluorescence, atomic absorption spectroscopy, biosensor, colorimetric, and resonance scattering have been developed for the detection of Hg 2+ . However, compared to these methods, surface‐enhanced Raman scattering (SERS) with its extremely high surface sensitivity and fingerprint information about the chemical structures has attracted increasing attention in various areas, including food safety, biology, biomedical diagnostics, and chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…The environmental pollution caused by mercury ion has become a global problem; therefore, developing a sensitive and selective method for the detection of Hg 2+ ions is very necessary. Until now, numerous detection methods based on fluorescence, atomic absorption spectroscopy, biosensor, colorimetric, and resonance scattering have been developed for the detection of Hg 2+ . However, compared to these methods, surface‐enhanced Raman scattering (SERS) with its extremely high surface sensitivity and fingerprint information about the chemical structures has attracted increasing attention in various areas, including food safety, biology, biomedical diagnostics, and chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Metal ion-specific DNAs are those specific nucleic acid sequences of which certain DNA bases can selectively bind with metal ions to form strong metal-base complexes. Two of the most impressive DNAs of this type are thymine (T)-rich DNA that selectively binds Hg 2+ to form T-Hg 2+ -T mismatch (Miyake et al, 2006;Wu et al, 2011) and cytosine (C)-rich DNA that selectively binds Ag + to form C-Ag + -C mismatch (Ono et al, 2008;Zhan et al, 2012). Both of these two mismatches are belong to coordination bonds, and previous studies show that the T-Hg 2+ -T mismatches are more stable than the natural adenine-thymine (A-T) base pair with a binding constant close to 10 6 M -1 (Torigoe et al, 2010).…”
Section: Common Types Of Fnas Used In Heavy Metal Ion Detectionmentioning
confidence: 99%
“…In the first category, we study the conduction, capacitance or resistance, while in optical devices, changes in light (absorption and emission) are evaluated, and finally, mechanical sensors are mass and frequency-sensitive devices [23]. In addition to methods based on solid supports, label-free assays can also be performed directly in solution and are mostly coupled to optical detection.The best example of these assays are sensors based on the switchable structure of aptamers, aptamer DNAzymes and/or chemical of physical properties of nanoparticles [24]. Bulbul et al reported an optical aptasensor based on the alteration of the catalytic activity of redox active nanoceria and the conformational change of OTA aptamer upon target binding [25].…”
Section: Why Label-free Detection?mentioning
confidence: 99%